Evaluating the planktic foraminiferal B/Ca proxy for application to deep time paleoceanography - Haynes, Laura L.; Hönisch, Bärbel; Holland, Kate; Rosenthal, Yair; Eggins, Stephen M. (Earth and planetary science letters, 2019)
The Cenozoic Era has been characterized by large perturbations to the oceanic carbon cycle and global climatic changes, but quantifying the magnitude and cause of these shifts is still subject to considerable uncertainty. The boron/calcium (B/Ca) ratio of fossil planktic foraminifera shells is a promising tool for reconstructing surface ocean carbonate chemistry during such events. Previous studies indicate that symbiont-bearing, planktic foraminiferal B/Ca depends on the [B(OH)4−/DIC] ratio of seawater and potentially, when combined with foraminiferal δ11B proxy reconstructions of B(OH)4−, an opportunity to reconstruct surface ocean DIC in the geologic past. There are, however, two barriers towards interpreting records from the pre-Pleistocene era: (1) changes in seawater major ion chemistry in the past might have affected foraminiferal B/Ca; and (2) modern foraminifera species show variable B/Ca calibration sensitivities that cannot be constrained in now-extinct species. Here we address these challenges with new experiments in which we have cultured modern, symbiont-bearing foraminifera Globigerinoides ruber (pink) and Trilobatus sacculifer in seawater with simulated early Cenozoic seawater chemistry (high [Ca], low [Mg], and low [B]T). We explore mechanisms that can account for the inter-species trends that are observed in foraminiferal B/Ca, and propose a framework that can be used to apply B/Ca calibrations to now-extinct species for reconstructing climate perturbations under varying seawater chemistries. •Paleocene seawater chemistry affects planktic foraminifer boron/calcium proxy sensitivity.•T. sacculifer and O. universa shell boron content is similar to that of Paleogene species.•We present a new framework for applying B/Ca calibrations to the early Cenozoic.•Our new approach allows application of calibrations from modern species to extinct ones.